Inserts Coating Influence on Residual Stress of Turned Outer Bearings - Kordik, Marek; Struharnansky, Jozef; Martikan, Anton; Stancekova, Dana; Kusmierczak, Sylvia; Martinček, Juraj (Manufacturing Technology Journal, 2016)
Residual stresses significantly affect the life of parts material, especially in bearing manufacturing, where the stress introduced into the material in the manufacturing process affect the component throughout its whole operating life. It is therefore important to know the size and orientation of these stresses and to optimize the production process of the bearing rings, in order to eliminate as many of these undesirable stresses. The subject of the article is chosen at demand of practice and has to correlate coating cutting tool for residual stress and microstructure in turning the outer bearing rings made of material 1.3520, which is widely used in bearing production. Turning cutting tool WNMG 080408E-M was used with two different coatings. We conducted measurements on a X-ray diffractometer. We measured normal stress parameter and the FWHM (full width half maximum at), which is decisive, and it is related to the grain size of the material. We found that the residual axial stress approaching the zero value, depending on the etched layer.
Keywords: residual stresses; bearing rings; coatings; inserts